Culturing and Neuronal Differentiation of Human Dental Pulp Stem Cells. Issue 11 (24th November 2022) - Goorha, Sarita; Victor, A. Kaitlyn; Reiter, Lawrence T.
Abstract: A major issue in studying human neurogenetic disorders, especially rare syndromes affecting the nervous system, is the ability to grow neuronal cultures that accurately represent these disorders for analysis. Although there has been some success in generating induced pluripotent stem cells (iPSC) from both skin and blood, there are still limitations to the collection, production and use of iPSC derived neurons. We have had significant success in collecting and growing human dental pulp stem cells (DPSC) from exfoliated teeth sent directly to our laboratory by the parents of children with a variety of rare neurogenetic syndromes. This protocol outlines our current methods for the growth and expansion of DPSC from exfoliated (baby) teeth. These DPSC can be differentiated into a variety of cell types including osteoblasts, chondrocytes, and mixed neuron and glial cultures. Here we provide our protocol for the differentiation of early passage DPSC cultures into neurons for molecular and cellular studies. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Collection and transportation of exfoliated teeth Basic Protocol 2 : Dental pulp extraction Basic Protocol 3 : Passage, freezing, and thawing of DPSC cultures Basic Protocol 4 : Differentiation of DPSC into mixed neuronal cultures